2016
DOI: 10.18632/oncotarget.10506
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific metabolic interactions between liver and adipose tissue in MCD diet-induced non-alcoholic fatty liver disease

Abstract: Higher susceptibility to metabolic disease in male exemplifies the importance of sexual dimorphism in pathogenesis. We hypothesized that the higher incidence of non-alcoholic fatty liver disease in males involves sex-specific metabolic interactions between liver and adipose tissue. In the present study, we used a methionine-choline deficient (MCD) diet-induced fatty liver mouse model to investigate sex differences in the metabolic response of the liver and adipose tissue. After 2 weeks on an MCD-diet, fatty li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 50 publications
2
35
0
Order By: Relevance
“…Previously, a sex-specific activation of Fgf21 expression was observed in humans and animals with various metabolic diseases (Wang et al, 2017;Chukijrungroat et al, 2017;Lee et al, 2016;Gasparin et al, 2018). Our results are in line with data from Gasparin and coauthors (Gasparin et al, 2018), who found that DIO increased Fgf21 mRNA expression in the liver, WAT and BAT in male, but not female mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previously, a sex-specific activation of Fgf21 expression was observed in humans and animals with various metabolic diseases (Wang et al, 2017;Chukijrungroat et al, 2017;Lee et al, 2016;Gasparin et al, 2018). Our results are in line with data from Gasparin and coauthors (Gasparin et al, 2018), who found that DIO increased Fgf21 mRNA expression in the liver, WAT and BAT in male, but not female mice.…”
Section: Discussionsupporting
confidence: 92%
“…Wang et al (2017) found that higher serum FGF21 levels were associated with an increased risk of type 2 diabetes in Chinese women but not in men. Diets that induce NAFLD also affected hepatic Fgf21 expression in sex-specific manners: highfat high-fructose diet increased Fgf21 expression only in male rats (Chukijrungroat et al, 2017), methioninecholine deficient diet only increased expression in female mice (Lee et al, 2016) and cafeteria obesogenic diet only increased expression in male mice. It is unknown whether the sex differences in the expression of FGF21 are manifested only in metabolic diseases and, possibly, are a consequence of these diseases, or if the activation of Fgf21 expression is sex-specific under natural physiological adaptations to nutritional stresses.…”
Section: Introductionmentioning
confidence: 99%
“…43 In fact, the accumulation of hepatic lipids and the consequent development of liver steatosis are twice as common in the postmenopausal period compared to the reproductive age. [44][45][46] In addition, mice fed with a diet deficient in choline and methionine for two weeks show steatosis, an increase in hepatic transaminases, and an increased expression of inflammatory markers with these changes more pronounced in males, 47 corroborating our present findings where EW females did not have alterations in liver morphology or in serum and hepatic CHOL and TG levels.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, the Hif-p4h-2 gt/gt mice on the HF-MCD diet had less WAT, and interestingly, they showed improved browning of WAT, which was associated with increased heat production. This likely contributed to less hepatic steatosis in the Hif-p4h-2 gt/gt mice, as WAT browning protecting against NAFLD has been reported on an MCD diet [28,29]. However, this is the first report associating HIF-P4H inhibition with induced browning of WAT and increased thermogenesis, while earlier reports associate environmental hypoxia with HIF pathway activation and WAT browning [43,44].…”
Section: Discussionmentioning
confidence: 65%
“…Browning of WAT has been shown to be a protective mechanism against NAFLD in mice on MCD diet [28,29]. Therefore, we next studied the expression of uncoupling protein 1 (UCP1) in the WAT of the HF-MCD diet-fed mice.…”
Section: Increased Heat Production In the Hif-p4h-2-deficient Mice Onmentioning
confidence: 99%